Analisis Makna Bentuk Verba Keinginan Bahasa Jepang pada Mahasiswa Bahasa Jepang Universitas Harapan Medan: Array (Universitas Harapan Medan, 2022)
Abstract This study discusses the analysis of the meaning of Japanese language desire verbs for Japanese students at University Harapan University, Medan. The research problem is what kind of meaning is there in the sentences hoshii and tai. This study aims to determine the meaning of hoshii and tai on the assignment of Japanese students at Harapan University, Medan. The method used in collecting data in this study is the method descriptive qualitative. The data used in this research is the assignment of 2nd and 3rd year students majoring in Japanese, Harapan University, Medan Hoshii is an auxiliary verb that expresses the hope or desire of the first person or speaker which is used to express hope or desire for something. Tai is a type of auxiliary verb that is used to express the wishes or expectations of the speaker, interlocutor, and the person being spoken of. The results that have been found in this study are that in sentences containing hoshii, students prefer an object. There are those who want to have a new laptop, they want to have a new house, they want to have a new TV, they want a car and others. While sentences containing tai, the students are more in the form of actions or activities. There are students who want to go to play with friends, want to meet Japanese friends, want to buy new clothes and others.